2021
DOI: 10.3389/fmed.2021.641746
|View full text |Cite
|
Sign up to set email alerts
|

Neuropathic Itch: Routes to Clinical Diagnosis

Abstract: Neuropathic itch occurs due to damage of neurons of the peripheral or central nervous system. Several entities, including metabolic, neurodegenerative, orthopedic, infectious, autoimmune, malignant, and iatrogenic conditions, may affect the somatosensory system and induce neuropathic itch. Due to the complex nature of neuropathic itch, particularly concerning its clinical presentation and possible etiological factors, diagnostic work-up of this condition is challenging. A detailed medical history, especially i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 59 publications
1
27
0
Order By: Relevance
“…As a result of a multicentre study on 391 diabetic outpatients, Yamaoka et al [ 8 ] proved that prevalence of TPUO in diabetic subjects was significantly higher than that in age-matched nondiabetic subjects (11.3 vs. 2.9%, p = 0.0001). In our study, besides itching, patients usually also reported other sensations, such as tingling, numbness, stinging or burning, clinically connected to SFN and neuropathic itch [ 42 , 43 ]. Patients without itch had significantly lower possibility of neuropathy compared with itchy subjects, while clinically visible neuropathy was more frequent in the itchy group.…”
Section: Discussionmentioning
confidence: 99%
“…As a result of a multicentre study on 391 diabetic outpatients, Yamaoka et al [ 8 ] proved that prevalence of TPUO in diabetic subjects was significantly higher than that in age-matched nondiabetic subjects (11.3 vs. 2.9%, p = 0.0001). In our study, besides itching, patients usually also reported other sensations, such as tingling, numbness, stinging or burning, clinically connected to SFN and neuropathic itch [ 42 , 43 ]. Patients without itch had significantly lower possibility of neuropathy compared with itchy subjects, while clinically visible neuropathy was more frequent in the itchy group.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, specific symptoms, such as itching, tingling and intraoral foreign body sensation, are considered part of a peripheral somatosensorial neuropathy [ 30 ]. Instead, the presence of globus pharingeus could be explained in a different way.…”
Section: Discussionmentioning
confidence: 99%
“…Small-fiber neuropathy caused by damage to the peripheral nervous system of myelinated Aδ-fibers and unmyelinated C-fibers [ 15 ] is one of the conditions causing neuropathic itch, which occurs due to injury of neurons of the peripheral or central nervous system [ 16 ]. Neuropathic itch has been demonstrated to play a role in a range of itchy disorders [ 17 ] and DM-associated sensory neuropathy [ 18 ], suggesting that peripheral nerve damage in the inflammatory course of DM may contribute to the mechanism of DM-related pruritus. However, further large studies are required into the association of small-fiber neuropathy and DM-related pruritus.…”
Section: Dermatomyositis (Dm)mentioning
confidence: 99%
“…Small-fiber neuropathy has been demonstrated in primary SS and higher neuropathic symptom burden compared to other well-known small-fiber neuropathy etiologies, hereditary transthyretin amyloidosis and idiopathic small-fiber neuropathy [ 71 ]. Therefore neuropathic itch may be involved in pruritus of patients with SS [ 17 ]. Due to the unclear pathogenesis of pruritus in SS, specialized pruritus therapy is sparse.…”
Section: Sjögren Syndrome (Ss)mentioning
confidence: 99%